Prevalence, genomic characterization and antimicrobial resistance of Campylobacter spp. isolates in pets in Shenzhen, China - Ju, Changyan; Ma, Yanping; Zhang, Bi; Zhou, Guilan; Wang, Hairui; Yu, Muhua; He, Jiaoming; Duan, Yongxiang; Zhang, Maojun (Frontiers in Microbiology, 2023)
The prevalence of Campylobacter spp.in pets is a potential concern for human health. However, little is known about the pet-related Campylobacter spp. in China. A total of 325 fecal samples were collected from dogs, cats, and pet foxes. Campylobacter spp. were isolated by culture, and MALDI-TOF MS was used to identify 110 Campylobacter spp. isolates in total. C. upsaliensis (30.2%, 98/325), C. helveticus (2.5%, 8/325), and C. jejuni (1.2%, 4/325) were the three found species. In dogs and cats, the prevalence of Campylobacter spp. was 35.0% and 30.1%, respectively. A panel of 11 antimicrobials was used to evaluate the antimicrobial susceptibility by the agar dilution method. Among C. upsaliensis isolates, ciprofloxacin had the highest rate of resistance (94.9%), followed by nalidixic acid (77.6%) and streptomycin (60.2%). Multidrug resistance (MDR) was found in 55.1% (54/98) of the C. upsaliensis isolates. Moreover, 100 isolates, including 88 C. upsaliensis, 8 C. helveticus, and 4 C. jejuni, had their whole genomes sequenced. By blasting the sequence against the VFDB database, virulence factors were identified. In total, 100% of C. upsaliensis isolates carried the cadF, porA, pebA, cdtA, cdtB, and cdtC genes. The flaA gene was present in only 13.6% (12/88) of the isolates, while the flaB gene was absent. By analyzing the sequence against the CARD database, we found that 89.8% (79/88) of C. upsaliensis isolates had antibiotic target alteration in the gyrA gene conferring resistance to fluoroquinolone, 36.4% (32/88) had the aminoglycoside resistance gene, and 19.3% (17/88) had the tetracycline resistance gene. The phylogenetic analysis using the K-mer tree method obtained two major clades among the C. upsaliensis isolates. All eight isolates in subclade 1 possessed the gyrA gene mutation, the aminoglycoside and tetracycline resistance genes, and were phenotypically resistant to six classes of antimicrobials. It has been established that pets are a significant source of Campylobacter spp. strains and a reservoir for them. This study is the first to have documented the presence of Campylobacter spp. in pets in Shenzhen, China. In this study, C. upsaliensis of subclade 1 required additional attention due to its broad MDR phenotype and relatively high flaA gene prevalence.